The Role of Embedded Librarians as Information Professionals: A Systematic Literature Review - Azkagina, Sakina Rofi; Irawati, Indira (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This study discusses the role of embedded Librarians as information professionals. Embedded librarian is someone who is proactive in providing library services in information retrieval and understands the information needs of its users. The development of information and communication technology (ICT) has also had a significant impact on education and research. However, the abundance of information sources is sometimes a problem for students or researchers who must choose and use appropriate and accurate sources of information. The Embedded Librarian concept refers to librarians who are actively involved in a particular group, build deep relationships with the group, and provide information services tailored to their needs. The method used is a systematic study with a qualitative approach, and selected articles sourced from Google Scholar and OnlineDatabase subscribed to the Library of the University of Indonesia http://remote-lib.ui.ac.id/). The analysis process consists of 6 (six) stages, namely 1) field mapping through scope review; 2) comprehensive search; 3) quality assessment; 4) data extraction; 5) synthesis; and 6) writing. The majority of the journal articles studied discussed the roles and activities of embedded librarians. This research provides a broader understanding of the development of information professionals and how the role of the Embedded Librarian evolves as information and technology evolves. This research also provides guidance on the skills and competencies required to become an effective Embedded Librarian. In practice, Embedded Librarian activities can be adapted to the environment and needs of the clients served, so as to provide relevant and effective information support